Eo-meo-ni - Tae, Jun-seek (South Korea, 2011)
On the narrow streets of Changsin-dong, Korea, there is a grandmother, Madame Lee So-seon. After the death of her son, Martyr Chun Tae-il, she stood by those who were living harsh lives, doing her best to always be upright and honest. This is the story of the last two years of her life.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films